102 Process Evaluation Exploring the Delivery and Uptake of Posture and Mobility Training for Staff in Care Homes. (6th February 2020) - Williams, R; Clarke, D; Graham, L; Hawkins, R; Cundill, B; Ellwood, A; Farrin, A; Fisher, J; Goodwin, M; Holland, M; Hull, K; Hulme, C; et al.
Abstract: Introduction: Provision of care for care home residents with complex needs is challenging. Physiotherapists can play a major role in enhancing the confidence, skills and abilities of care home staff. The Skilful Care Training Package (SCTP) aims to provide staff with an understanding of good posture and training in skilled facilitation of movement. This process evaluation explored barriers and facilitators to delivery and uptake of the SCTP within the context of a feasibility cluster randomised controlled trial (cRCT) in 10 care homes. Methods: A mixed methods process evaluation, incorporating non-participant observations and interviews, conducted in the five care homes receiving the SCTP intervention. Interviews were audio recorded and transcribed verbatim; resident conversations were captured via a Dictaphone and/or field-notes. Data analysis used the Framework approach. Results: Fourteen staff training sessions were observed. Interviews with 22 staff and four trainers, and 13 conversations with residents were completed. Five factors influenced delivery and uptake of the SCTP: Organisational factors: strategies to publicise and facilitate access to training improved attendance; a convenient training location and trainer flexibility encouraged attendance and staff engagement. Intervention delivery: a practical participatory element to the training was highly valued; adapting the training to meet the needs of the homes was well-received. Engagement and interaction: relating training to workplace and residents' experiences engaged staff; high levels of engagement and positive interaction within the training sessions were reported; challenges relating to staff hierarchy affected training delivery in some homes. Intervention content: posture and mobility elements were seen as important; however, some repetition with prior training was highlighted. Training impact: there were indications that staff adopted SCTP techniques. Staff reported an increase in their wellbeing and confidence in movement facilitation; cascade training was reported in some homes. Conclusions: Training was well-received, and feedback on its impact was largely positive. Practical elements were viewed favourably over classroom-based learning. Intervention content should be revised to optimise focus and avoid overlap with other training.